GwB, A Workbench for Natural Language Grammars - Branco, António Horta (2009)
As an intermediate instrumental step in our research on reference processing and binding theory, we built up a grammar workbench which we called GwB. This workbench was primarily designed as a computational tool to help verifying the theoretical consistency and the empirical adequacy of our working hypotheses. In this paper, we report on the architecture underlying GwB and its functionality. Firstly, we present the general language processing framework embodied in the grammar workbench. Secondly, we present a brief survey of the computational systems available for the implementation of that framework and discuss the major aspects of the implementation of GwB in the system we opted for